2008
DOI: 10.1080/10410230802465266
|View full text |Cite
|
Sign up to set email alerts
|

Meanings of Health: Interrogating Structure and Culture

Abstract: Based on the argument that context ought to be centralized in discourses of health communication, this article applies the culture-centered approach to engage in dialogue about issues of health with 18 men in rural West Bengal. The culture-centered approach is based on dialogue between the researcher and the community members, with the goals of listening to the voices of cultural members in suggesting culture-based health solutions. In this project, our discursive engagement with the participants suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(37 citation statements)
references
References 25 publications
0
37
0
Order By: Relevance
“…Most of the community-engaged research studies reviewed involved adults (4,9,17,18,20,22), with a few studies including adolescents (10,12). Some studies focused on improving the health and wellbeing of children and adolescents specifically (7,8,10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the community-engaged research studies reviewed involved adults (4,9,17,18,20,22), with a few studies including adolescents (10,12). Some studies focused on improving the health and wellbeing of children and adolescents specifically (7,8,10).…”
Section: Resultsmentioning
confidence: 99%
“…Although CBPR is advocated as a research strategy that is mutually beneficial to both researchers and community members and that improves community capacity and involvement (25), it is not fully clear whether the approach leads to better health outcomes. In a review of interventions designed using CBPR, studies that utilized a randomized controlled trial design indicated a positive effect on health (9). Those studies that utilized a quasiexperimental design had mixed findings (25).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Dutta and Pal (2010) theorize the role of dialog with subaltern communities as providing "discursive openings for the interrogation of dominant sites of knowledge production" (p. 363). Similarly, Dutta and Basu (2008) provide a theoretical and methodological warrant for dialog with marginalized communities in highlighting how co-construction allows for local meanings of health to emerge, challenging elite knowledge and categories. This paper addresses the ways that received academic knowledge about patient navigation was reshaped based on dialogic co-construction of the local relevance and meaning of physicians, volunteers, potential navigators, and other community resources required to develop a navigation program.…”
Section: Culture-centered Methodology and Dialogic Co-constructionmentioning
confidence: 99%
“…Furthermore, this study extends the theorizing on dialog within the CCA (Dutta and Basu, 2008;Dutta and Pal, 2010), by focusing on how dialog with marginalized communities can be the entry point to developing bottom-up health solutions. This emphasis on dialogic co-construction differentiates our study from existent patient navigation interventions.…”
Section: Contributions To Theorizing and Practice Of Patient Navigatimentioning
confidence: 99%
“…Unlike many health campaigns, which often modify universal messages to 'fit' other cultures and might invalidate the experiences of traditionally underserved populations, cultural grounding engages the target audience by calling upon them to articulate their own meaning, codes, and identity (Hecht and Lee 2008). These culture-centered approaches emphasize the need to understand how participants articulate health by engaging in dialogue and mutual understanding, and stress the importance of addressing social, cultural, and environmental factors beyond a biomedical model (Dutta and Basu 2008;Thomas et al 2004).…”
Section: The Principle Of Cultural Groundingmentioning
confidence: 99%